2020
DOI: 10.3390/ijerph17062060
|View full text |Cite|
|
Sign up to set email alerts
|

Do the Walkability and Urban Leisure Amenities of Neighborhoods Affect the Body Mass Index of Individuals? Based on a Case Study in Seoul, South Korea

Abstract: This study investigates the impact of neighborhood-built environments on obesity in interrelationship with socioeconomic status (SES)—controlling for dietary patterns and physical activities of residents—using structural equation modeling (SEM). A total of 577 samples who are between 19 and 64 years old and reside in Seoul are extracted from Korea National Health and Nutrition Examination Survey (KNHNES), 2015. Neighborhood environments are represented as the two latent constructs—walkability and leisure ameni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…The presence and accessibility of walking facilities are generally identi ed as supporting walking [30,31]. In contrast to studies suggesting higher walkability in high-SES areas, an inverse relationship was found in studies by Choi and Yoon [32] and Conderino et al [2]. The last study reported that on average, low-income neighbourhoods had higher walking scores than high-income ones.…”
Section: Results Focusing On Area Variablesmentioning
confidence: 98%
See 1 more Smart Citation
“…The presence and accessibility of walking facilities are generally identi ed as supporting walking [30,31]. In contrast to studies suggesting higher walkability in high-SES areas, an inverse relationship was found in studies by Choi and Yoon [32] and Conderino et al [2]. The last study reported that on average, low-income neighbourhoods had higher walking scores than high-income ones.…”
Section: Results Focusing On Area Variablesmentioning
confidence: 98%
“…linked local economic resources with the number of sports facilities and PA, especially among older individuals and women.Hillsdon et al [78] and studies from Asia[32,34] observed a positive association between SES and leisure amenity availability.Ferguson et al [79] and Lamb et al [80] showed that public transport access in low-income areas provides closer proximity to sports facilities, a difference nulli ed by car ownership. Panter et al [81] and Hillsdon et al [53] discussed how poor facility coverage in deprived English areas affects PA levels, with individuals often travelling beyond local areas for activity.…”
mentioning
confidence: 99%
“…This ensures that the parameter estimates remain unbiased. SEM provides a comprehensive, flexible approach for analyzing complex relationships between variables, making it valuable for validation or exploratory purposes [ 63 , 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar surveys exist in other countries. South Korea, for example, also conducts a national-level survey (i.e., Korea National Health and Nutrition Examination Survey [KNHNES]) [46]. (d) Mortality data: data on causes of death in the United States.…”
Section: Access Data From the National State And Local Surveysmentioning
confidence: 99%